MiR-182 prevented ototoxic deafness induced by co-administration of kanamycin and furosemide in rats. (1st April 2020) - Chen, Jun; Liu, Zhenzhen; Yan, Hui; Xing, Wei; Mi, Wenjuan; Wang, Renfeng; Li, Wei; Chen, Fuquan; Qiu, Jianhua; Zha, Dingjun
Highlights: miR-182 overexpression attenuated permanent threshold shifts in rats. miR-182 reduced the loss of outer hair cells and missing stereocilia. miR-182 could protect against acute ototoxic drug-induced deafness by elevating PI3K p85α levels in rats. Abstract: Ototoxic drugs may induce auditory sensory hair cell loss and permanent deafness; however, there is still no effective treatments or prevention strategies for this side effect. A recent study found that microRNA182 (miR-182) protected cochlear hair cells from ototoxic drug-induced apoptosis in vitro . However, it remains unclear whether miR-182 can protect drug-induced deafness in vivo . In this study, we overexpressed cochlear miR-182 in Sprague-Dawley rats by trans-round window niche delivery of miR-182 mimics. The rats subsequently received intraperitoneal injections of kanamycin and furosemide to induce acute cochlear outer hair cell death and permanent deafness. Auditory brainstem response tests showed that miR-182 attenuated permanent threshold shifts. Consistent with this result, miR-182 reduced the loss of outer hair cells and missing stereocilia. miR-182 treatment also increased the level of phosphoinositide-3 kinase regulatory subunit p85α in the outer hair cells after co-administration of kanamycin and furosemide. Our findings suggest that miR-182 has powerful protective potential against ototoxic drug-induced acute auditory sensory hair cell loss and permanent deafness.